Transmission Control of Electromagnetic Waves by Using Quarter-Wave Plate and Half-Wave Plate All-Dielectric Metasurfaces Based on Elliptic Dielectric Resonators - Ali Yahyaoui; Hatem Rmili; Karim Achouri; Muntasir Sheikh; Abdullah Dobaie; Adnan Affandi; Taoufik Aguili (International Journal of Antennas and Propagation)
We present the design of all-dielectric Quarter-Wave Plate (QWP) and Half-Wave Plate (HWP) metasurfaces based on elliptic dielectric resonators (EDRs) for the transmission control of electromagnetic waves over the frequency band 20–30 GHz. First, an extensive numerical analysis was realized by studying the effect of the resonators geometry (thickness and ellipticity) on the transmission of both x- and y-polarized waves. Then, based on the numerical analysis, we have realized and characterized experimentally both QWP and HWP all-dielectric metasurfaces.